Hypovolemic Shock And The Need For Invasive Mechanical Ventilation On A Patient With Congenital Heart Disease - Simoes, Marisa (2024)
Techniques of venoarterial-extracorporeal membrane oxygenation (VA-ECMO) have improved over the decades, with numerous applications.1 Those with reversible low cardiac output benefit most from this support.1 Case of 21-year-old male, history of congenital heart disease (severe right ventricle hypoplasia and pulmonary artery stenosis with extracardiac cavo-pulmonary shunt (Fontan surgery), and atrial septal defect). Brought to the Emergency Department due to a Mallory-Weiss syndrome, upper-endoscopy “laceration at esophagogastric junction (EGJ) with active bleeding”, clips were applied. However, worsening shock, repeated melenas and hematemesis, hemoglobin drop, lactate 2.8mmol/L, and needing noradrenaline (1.21mcg/kg/min). Due to active blood loss and worsening shock, the patient was intubated to maintain airway protection. Repeated upper-endoscopy “voluminous live red clot at EGJ, 4-clips and active bleeding of mucosa between, injection of polidocanol”. Despite the implemented strategy, high risk of rebleeding remained. Following invasive mechanical ventilation (IMV), sustained hypotension having to increase noradrenaline (1.52mcg/kg/min) and lactate (5.8mmol/l), despite fluid resuscitation. Echocardiogram evidenced severe ventricular dysfunction, and fixed inferior vena cava (IVC) of 20mm. The heart defect combined with positive intrathoracic pressure, contributed to the worsened shock, as Fontan circulation is dependent on low vascular resistance to maintain output2. Needing VA-ECMO and admitted to ICU, volemia optimization, adjusting ventilation to lower intrathoracic pressure and started on milrinone and sildenafil. Another upper-endoscopy showed laceration at EGJ, with placement of clips. Echocardiogram revealed “Normal left ventricle. Hypoplastic right ventricle. Mild mitral regurgitation; aortic VTi 19cm. IVC 22mm. RV/RA gradient 70mmHg. Interatrial bidirectional shunt”. Favorable evolution permitted extubation, suspension of milrinone and sildenafil, followed by decannulation. With rescue ECMO, congenital heart disease are salvageable despite sudden decompensation3. This case, positive intrathoracic pressure impairs the Fontan circulation, dependent on preload and higher central venous pressure to maintain cardiac output, as the ventricle is unable to compensate increased demands2, and worsening shock.